1995
DOI: 10.1046/j.1471-4159.1995.64020624.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Lumped Constant for the α‐Methyltryptophan Method of Estimating the Rate of Serotonin Synthesis

Abstract: The lumped constant (LC) for the α‐methyl‐l‐tryptophan method to convert the brain's uptake of labeled α‐methyl‐l‐tryptophan into the regional rate of serotonin synthesis was estimated. The method involved independently estimating the unidirectional uptake constant of the tracer (α‐[14C]methyl‐l‐tryptophan) to the tissue and the tracee (tryptophan) (with the addition of a radioactive compound) and calculating their ratio. The LC was estimated from logarithmically transformed data. Similar experiments were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 24 publications
3
52
2
Order By: Relevance
“…The rate of 5-HT synthesis (R; pmol/g/min) was calculated by converting K (slopes obtained from volume of distribution fit as a function of exposure time ; here Cp*(t) and C*p(T) are plasma tracer concentration as a function of time (t) and at the end of experiment (T), respectively) to K T (K T = K/LC; division by the lumped constant (LC)) and then multiplying the calculated K T by the plasma free (non-protein-bound) Trp (Cp; pmol/mL); R = CpK/LC = CpK T . The LC for α-MTrp used in the present study was previously measured in vivo and found to be 0.42 ± 0.07 [52], and it is not influenced by drugs [41,52].…”
Section: Calculation Of the 5-ht Synthesis Ratementioning
confidence: 55%
“…The rate of 5-HT synthesis (R; pmol/g/min) was calculated by converting K (slopes obtained from volume of distribution fit as a function of exposure time ; here Cp*(t) and C*p(T) are plasma tracer concentration as a function of time (t) and at the end of experiment (T), respectively) to K T (K T = K/LC; division by the lumped constant (LC)) and then multiplying the calculated K T by the plasma free (non-protein-bound) Trp (Cp; pmol/mL); R = CpK/LC = CpK T . The LC for α-MTrp used in the present study was previously measured in vivo and found to be 0.42 ± 0.07 [52], and it is not influenced by drugs [41,52].…”
Section: Calculation Of the 5-ht Synthesis Ratementioning
confidence: 55%
“…We chose to use plasma free Trp in this calculation because of the reports indicating that this plasma fraction is in dynamic equilibrium with brain Trp (Bloxam and Curzon 1978;Salter et al 1989;Takada et al 1993). The LC was measured in vivo and found to be homogenous throughout the brain and has a value of 0.42±0.07 (Vanier et al 1995). In the present experiments, all of the linear relationships between Θ and DV* had a significant (p<0.05; F-statistics) and positive slope (Nagahiro et al 1990).…”
Section: Calculation Of the α-Mtrp Trapping And 5-ht Synthesis Ratesmentioning
confidence: 72%
“…After conversion into the volume of distribution (VD [ml/g]; division of tissue radioactivity by plasma tracer concentration (Cp; nCi/ml) at the time of euthanasia), the slope of the unidirectional net uptake of the tracer, required in the rate calculation, was calculated from the linear relationship between VD (ml/g) and exposure time Θ (Θ=∫Cp.dt/Cp(T) [min] (see details in Nagahiro et al 1990; Diksic et al 1995; Diksic and Young, 2001). The LC of 0.42 measured in the rats was used in the calculations (Vanier et al 1995). …”
Section: Methodsmentioning
confidence: 99%